2020
DOI: 10.1177/1538574420975556
|View full text |Cite
|
Sign up to set email alerts
|

Bowstring Phenomenon in Renal Artery Aneurysm Exclusion Using a Viabahn Stent Graft

Abstract: A 77-year-old man presented with an incidental finding of right renal artery aneurysm without symptoms. Computed tomography revealed a 22 mm saccular aneurysm with a wide neck at the main renal artery trunk. An 8 × 100 mm Viabahn stent graft (W. L. Gore, Flagstaff, AZ) was deployed by fully pulling back the guiding sheath. However, the deployment knob was not able to be pulled. We returned the guiding sheath to the original position and confirmed the cause was the bowstring phenomenon. Because avoidance of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…This technique is extremely effective in preventing the risk of vessel injury and facilitating distal advancement of the guiding sheath. 12 Miyayama et al 13 reported that ultraselective TACE was effective in controlling local recurrence, especially when accumulating dense iodized oil emulsion in HCC with a greater grade of portal vein visualization. As we routinely tried to advance the microballoon catheter as much as possible to the distal portion of the feeding artery (e.g., the distal subsegmental and distal sub-subsegmental tumor feeding branches), we performed CHA insertion in all patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique is extremely effective in preventing the risk of vessel injury and facilitating distal advancement of the guiding sheath. 12 Miyayama et al 13 reported that ultraselective TACE was effective in controlling local recurrence, especially when accumulating dense iodized oil emulsion in HCC with a greater grade of portal vein visualization. As we routinely tried to advance the microballoon catheter as much as possible to the distal portion of the feeding artery (e.g., the distal subsegmental and distal sub-subsegmental tumor feeding branches), we performed CHA insertion in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Kawaguchi et al 11 used this technique on endoscopic retrograde cholangiopancreatography with a large balloon catheter. In the field of abdominal surgery, we reported the BAT as a “balloon anchoring and squeezing technique” (Saiga et al 12 , p. 403) in a case of renal artery aneurysm exclusion using a stent graft. This technique is extremely effective in preventing the risk of vessel injury and facilitating distal advancement of the guiding sheath.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation